Pengaruh Metode Analisis Stabilitas Lereng 3D terhadap Faktor Keamanan dan Kebutuhan Perkuatan pada Timbunan di Atas Tanah Lunak - Aisiyah Pramaisela Hapsari; Queen Arista Rosmania Putri Sumarsono (Jurnal Talenta Sipil, 2026)
Three-dimensional (3D) slope stability analysis is increasingly used in geotechnical planning because it is able to represent landslide conditions more closely than two-dimensional (2D) analysis. Differences in results between analytical methods and software have the potential to result in different reinforcement requirements. This study aims to compare the three-dimensional slope safety factor values obtained using the analytical method with the Hovland formula and Plaxis LE software and evaluate their influence on the need for geotextile reinforcement. The analysis was conducted using the three-dimensional Limit Equilibrium Method (LEM) on several variations in width, height, slope, and the ratio of the length of the landslide plane to the height of the embankment. The results showed that the 3D safety factor values ranged from 0.461 to 1.512. A comparison between the safety factors obtained from the analysis and the Hovland method showed that the ratio varied between 0.256 and 1.618, indicating a considerable difference in safety factor values between the PLAXIS LE 3D results and the Hovland method. The required geotextile reinforcement ranged from 0 to 37 layers and increased with increasing ls/H values, embankment width, and embankment height. The results of the study show that the selection of the three-dimensional slope stability analysis method influences the safety factor and the need for geotextile reinforcement, so it needs to be considered in the geotechnical planning process.